Splenectomy is not associated with a higher tricuspid regurgitant jet velocity in people with sickle cell anemia. Issue 10 (19th July 2019) - Sinha, Arpan A.; Adusumilli, Tanvi; Cohen, Hillel W.; Nouraie, Mehdi; Little, Jane; Manwani, Deepa
Abstract: Background: Vascular complications such as pulmonary hypertension (PH) occur at an increased rate following splenectomy in patients with various hemolytic blood disorders including thalassemia. The goal of this retrospective cross‐sectional analysis was to assess the independent association of splenectomy with an elevated tricuspid regurgitation velocity (TRV) in people with homozygous sickle cell disease (HbSS). TRV is a noninvasive screening test for PH and a surrogate marker of prognosis in sickle cell disease (SCD). Procedure: Data were obtained from the multicenter Walk‐PHaSST (treatment of pulmonary hypertension and sickle cell disease with sildenafil therapy) study of PH (NCT00492531). We compared TRV in the cohort of patients with HbSS who were surgically splenectomized with patients who were not surgically splenectomized. Results: We found no significant differences in TRV between the two groups. Conclusions: The lack of difference in TRV between the two groups is most likely because members of the comparator nonsurgical group in many cases experienced autoinfarction of the spleen in childhood. Splenectomy does not seem to confer additional risk for the development of a higher TRV in HbSS, unlike in patients with thalassemia or other hemolytic anemias. This could be an important consideration when weighing the risks and benefits of splenectomy in patients with HbSS.